The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1155/2016/3262790
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the In Vivo Therapeutic Effects of Radix Paeoniae Rubra Ethanol Extract with the Hypoglycemic Activities Measured from Multiple Cell‐Based Assays

Abstract: Background. Radix Paeoniae Rubra (Chi Shao) contains several phytochemicals with hypoglycemic actions. Current research aims to explore potential insulinotropic effects and long-term therapeutic efficacy of such herb against type 2 diabetes. Methods. Composition analysis for the ethanol extract (PRExt) was executed by high performance liquid chromatography. Polyphenol-enriched fraction was characterized by high pressure size exclusion chromatography. Multiple cell platforms were employed to evaluate hypoglycem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Recently, studies have demonstrated that traditional Chinese medicine may be effective in the prevention and treatment of myocardial I/R injury ( 7 , 8 ). According to traditional Chinese medicine, Radix Paeoniae Rubra, the dried root of Paeonia lactiflora Pall, is able to reduce heat and cool blood, disperse stasis and relieve pain ( 9 11 ). Total paeony glycoside (TPG) is a major component of Radix Paeoniae Rubra, and the effective component of TPG is a monoterpene compound ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, studies have demonstrated that traditional Chinese medicine may be effective in the prevention and treatment of myocardial I/R injury ( 7 , 8 ). According to traditional Chinese medicine, Radix Paeoniae Rubra, the dried root of Paeonia lactiflora Pall, is able to reduce heat and cool blood, disperse stasis and relieve pain ( 9 11 ). Total paeony glycoside (TPG) is a major component of Radix Paeoniae Rubra, and the effective component of TPG is a monoterpene compound ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Total paeony glycoside (TPG) is a major component of Radix Paeoniae Rubra, and the effective component of TPG is a monoterpene compound ( 12 ). Modern pharmacological studies have demonstrated that Radix Paeoniae Rubra has various pharmacological functions that mainly produce effects on the cardiovascular system ( 9 , 13 , 14 ). In addition, it exerts antitumor and anti-endotoxin effects, as well as other functions ( 9 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two anomers of pentagalloyl glucose prevented the conversion of preadipocytes to mature adipocytes (Ren, Himmeldirk, & Chen, 2006). When the activity of penta‐ O ‐galloyl‐D‐glucopyranose on BRIN‐BD11 cells, which are responsible for the releasing of the insulin, was investigated, it was shown that penta‐ O ‐galloyl‐D‐glucopyranose showed the insulinotropic effect in a dose‐dependent manner (Chang et al., 2016). The activities of α and β anomers of penta‐ O ‐galloyl‐D‐glucopyranose on stimulation of glucose transport were investigated, so the EC50 value of α and β pentagalloyl glucose was found to be 17 and 18 µM, respectively (Klein, Kim, Himmeldirk, Cao, & Chen, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This fact was not a surprise because many papers describing heat damage to polyphenols availability have been published. Losses of between 16 and 28% of polyphenol levels after pasteurization have been previously reported in grape and watermelon juice and strawberry puree [ 41 , 42 , 43 , 44 ]. The really important fact is that this loss is not considered relevant, since the remaining polyphenols are sufficient to induce healthy in vivo effects [ 45 ].…”
Section: Discussionmentioning
confidence: 99%